The Relationship Between Early Marriage and Parenting Styles for Children Aged 3-5 Years - Yastutik, Baiq Wiwik; Sulaiman, Lalu; Khalik, Lalu Abdul (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to investigates the link between early marriage and parenting styles among parents of children aged 3-5 years in Awang Village, Central Lombok, Indonesia. This study employs an observational analytic design with a cross-sectional approach. Data were gathered from 42 mothers who married before the age of 20. The research instrument is a questionnaire to collect information about socio-demographic and parenting style information, categorized as democratic, authoritarian, and permissive. Data analysis was conducted in two stages: univariate and bivariate analysis. The results of this study are that (1) a significant association between early marriage and authoritarian parenting styles, with 55% of mothers who married at or below 15 years old displaying authoritarian behavior, and 80% exhibiting permissive tendencies, (2) democratic parenting was exclusive to mothers who married at 16 years or older. Higher education levels were linked to democratic parenting, (3) a significant relationship between early marriage and authoritarian parenting, proven by statistical analysis using Fisher’s Exact Test (p = 0.001). The results suggest that early marriage leads to less supportive and more controlling parenting practices, negatively impacting child development. Thus, addressing socio-economic factors and improving educational opportunities are vital to mitigating the adverse effects of early marriage on parenting styles and child development.